Pregnant mother's knowledge level and its determinant factors towards preventable risk factors of congenital anomalies among mothers attended health institutions for antenatal care, Ethiopia - Getu Engida wake; Girma Wogie Fitie; Seada Endris; Shiferaw Abeway; Gebremaryam Temesgen (Elsevier, 2022)
Background: More than 90% of congenital anomalies occur in low and middle-income countries because of different risk factors. This study aimed to assess pregnant mothers' knowledge level and its determinant factors towards preventable risk factors of congenital anomalies among mothers attended health institutions for antenatal care in Dessie town, Ethiopia. Methods: Health institution-based cross-sectional study design was conducted among 404 pregnant mothers in Dessie town, Ethiopia from 12 January 2020 to 12 March 2020. A systematic random sampling method was used to get selected mothers. Epidata version 3.1 and, and SPSS version 20 were used for data entry and analysis respectively. Results: A total of 404 pregnant mothers were included with a 100% response rate. The overall good knowledge of pregnant mothers towards preventable risk factors of congenital anomalies was 211(52%).Four or more antenatal care visits [adjusted OR = 2.93, 95% CI: 1.696-5.072,P-value <0.001], urban residence [ adjusted OR = 5.97, 95% CI: 2.95-12.078,P-value <0.001], monthly family income of more than 4500 ETB [adjusted OR = 5.52, 95% CI: 1.616-18.861,P-value <0.006] and secondary school and above [adjusted OR = 4.29, 95%CI: 2.464-7.467, P- value < 0.001] were significant associated factors with pregnant mothers knowledge. Conclusion: More than half of pregnant mothers had good knowledge of preventable risk factors of congenital malformation. Governmental and non-governmental health institutions should create a conducive environment for health care providers to create awareness regarding preventable risk factors of congenital malformation for all couples, pregnant mothers, and the community as a whole.